Urgensi Pengaturan Artificial Inteligence Dalam Transaksi Bisnis Digital di Indonesia - Buala Jefry (Riviera Publishing, 2025)
The rapid development of Artificial Intelligence (AI) has transformed digital business transactions in Indonesia, outpacing current legal frameworks. This paper provides a normative legal analysis of the need to regulate AI in digital commercial transactions through a study of statutes, doctrine, and practice. The study identifies a legal vacuum concerning recognition of AI-generated acts, liability attribution, and consumer/data protection. To address these gaps, the paper recommends: (1) statutory definition of AI and a limited electronic agent status; (2) a liability regime combining strict liability for high-risk applications with attribution rules for developers and deployers; (3) mandatory algorithmic transparency and stronger data protection; and (4) creation of an intersectoral technical-legal oversight body. Regulating AI is essential to ensure legal certainty, accountability, and fairness in Indonesia’s digital economy.